REVITALIZATION OF BOARDING SCHOOL CURRICULUM IN IMPROVING THE QUALITY OF STUDENTS - Nofitasari, Dian Evy; Abdillah, Ikhwan; Hidayatullah, Mohammad Alief (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2024)
In Islamic boarding schools, curriculum revitalization is very important in improving the quality of students. The objectives of curriculum revitalization in improving the quality of students are: 1. Improving the quality of education, 2. Strengthening the integration of religious and general education, 3. Increasing the competitiveness of students, 4. Preparing students to become agents of change. Here, Islamic boarding schools not only maintain the noble teachings of Islam but also integrate them with modern science. Islamic boarding school administrators need to realize that students need to be equipped with relevant skills to face the global world. Islamic boarding schools formulate new curriculum in a mature manner and involve many parties to gather to discuss what should be maintained and what should be added by conducting comparative studies of Islamic boarding schools that have been successfully reformed. It is interesting that many Islamic high schools involve successful alumni in various fields to contribute. This ensures that the implementation of curriculum revitalization is not only innovative but also in accordance with the principles of Islamic boarding schools. This study uses a qualitative approach. The researcher provides a detailed explanation of the findings related to the revitalization of the Islamic boarding school curriculum in this study. To obtain complex data, researchers can explain all symptoms or conditions in the field and obtain information and data sources. The Findings Aspect of this Research is the renewal of the Islamic boarding school curriculum is the integration of general knowledge with religious knowledge. For example, students learn theory and how science supports the truth of the Koran in science class. Both the world economy and the Islamic economic system are covered in economics class. Students are taught how to use social media for preaching even in technology classes. Students learn from this integrative method that in Islam, religious knowledge and general knowledge cannot be separated from each other.